IMPLEMENTASI MANAJEMEN RANTAI PASOKAN PADA UMKM KOPERASI GARUDAYAKSA NUSANTARA, JAKARTA - Abdulah Rakhman; Liaw Bun Fa; M. Fuad; Bernadine; Hafizah Rifiyanti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Micro, Small and Medium Enterprises (MSMEs) must be recognized as a strategic and important force to accelerate regional development, because the growth of Micro, Small, and Medium Enterprises is increasing every year, where the number of MSMEs in Indonesia in 2020 is 64.2 million units, and proven contributes 61 percent to GDP (Gross Domestic Income) (Airangga, 2021). MSME problems include financial and non-financial problems. To overcome these MSME problems, supply chain management can be implemented by implementing several activities, namely (1) management of managerial aspects aimed at increasing productivity, marketing capabilities, and human resource development, (2) capital aspects by collaborating with banks, and (3) partnership program to increase cooperation with suppliers and consumers. MSMEs who are members of the Garudayaksa Nusantara Cooperative in dealing with MSME problems apply the concept of supply chain management by choosing a few suppliers and an efficient distribution channel model, namely supplier-UMKM-consumer.